FACTORS DRIVING CUSTOMER SATISFACTION AND LOYALTY IN SPORTS AND HEALTH CENTRE - Mizhgon, Bakhti; Supardi; Abd Razak, Anis (International Journal of Psychosocial Rehabilitation, 2020)
It was highlighted that the numbers of customer dropout in the sports and health center becoming high ever since there are many players in the market. The high numbers of dropout are a loss to service providers as they are not able to keep the customers for repeat visit. Business organizations cannot afford to let the situations to happens repeatedly without knowing what exactly the customers do is looking for and needs. This study is about the drivers of customer satisfaction with the intention to measure the attention to customer and personnel support at the sports and health centre in major cities of Indonesia. These study employ questionnaires to collect data. Data were collected using hybrid method combination of online and face to face. 500 survey forms distributed with a response rates of 68.2%. The data was analyzed using structural equation model and results indicates that both attention to customer and personnel support are equally important towards keeping customer loyalty. Industry players in the market should consider this establishment’s as important as the results indicates the direct relationship between attention to customer and personnel support is stronger towards customer loyalty rather than the relationship between customer satisfaction towards customer loyalty. Hence, service provider needs to carefully design their customer experiences in order to provide the best services to their customer and visitors. Most importantly is to reduce the dropout rates and increase customer retentions.